Anomalous anti-Stokes Raman scattering during epoxy-amine polymerization - Robert V. Chimenti; Samuel E. Lofland (Polymer Testing)
In thermal equilibrium the Stokes Raman scatter should always be greater than the anti-Stokes; however, in some rare cases anomalous anti-Stokes Raman scattering (AASR) has been observed. This work presents the first observations of AASR during epoxy-amine polymerization and demonstrates the potential to utilize this phenomenon as a means of noncontact heat flow measurement. Even though the phonon population is unbounded, experimental evidence shows that the AASR can be phenomenologically explained from an entropic perspective as negative-absolute-temperature-like behavior. Furthermore, since polymerization is a non-equilibrium thermodynamic process, a statistical physics-based heat flow kinetics model was developed which simultaneously describes the observed AASR and allows for the extraction of the excess phonon population. This excess phonon population was combined with a simplified Debye model for the phonon density of states to calculate an effective heat flow, which closely corresponds to the heat flow measured by isothermal differential scanning calorimetry.